Generation and Characterization of Monoclonal Antibodies Against Rift Valley Fever Virus Nucleoprotein. (November 2013) - Fafetine, J. M.; Domingos, A.; Antunes, S.; Esteves, A.; Paweska, J. T.; Coetzer, J. A. W.; Rutten, V. P. M. G.; Neves, L.
Summary: Due to the unpredictable and explosive nature of Rift Valley fever (RVF) outbreaks, rapid and accurate diagnostic assays for low‐resource settings are urgently needed. To improve existing diagnostic assays, monoclonal antibodies (MAbs) specific for the nucleocapsid protein of RVF virus (RVFV) were produced and characterized. Four IgG2a MAbs showed specific binding to denatured nucleocapsid protein, both from a recombinant source and from inactivated RVFV, in Western blot analysis and in an enzyme‐linked immunosorbent assay (ELISA). Cross‐reactivity with genetically related and non‐related arboviruses including Bunyamwera and Calovo viruses ( Bunyaviridae family), West Nile and Dengue‐2 viruses ( Flaviviridae family), and Sindbis and Chikungunya viruses ( Togaviridae family) was not detected. These MAbs represent a useful tool for the development of rapid diagnostic assays for early recognition of RVF.